Panormos, Türkei: Die Arbeiten der Jahre 2012 und 2013 - Slawisch, Anja (e-Forschungsberichte des DAI, 2023)
Project Panormos is an international archaeological research project, centred on a recently-identified ancient necropolis near Didyma, located on the Aegean coast of Turkey. Since its establishment in 2012, the research has been undertaken as a cooperative effort between archaeological researchers from DAI’s Istanbul department and the archaeological Museum of Balat / Miletus (Aydın province, Turkey). The project aims to examine a number of historical issues, ranging from the lifestyles and geographical origins of the individuals who were buried at the necropolis, to recording and interpreting details of local/regional funerary practices, and to improving our knowledge of trade and interaction during the early 1st millennium BC.